Making globalization happen: the untold story of power, profits, privilege - Sripati, Vijayashri (New York, USA : Oxford University Press, 2023)
"This chapter demonstrates that Constitutional globalisation (Globalisation with a capital G) has emerged as a distinct field of policy analysis. Yet, because the classical liberal constitution's (Constitution) salience is not widely known, its globalisation in a world of sovereign states - in the post-colonial/post-Soviet era has escaped attention. Appraising Globalisation's legitimacy and impact therefore requires first fully understanding the Constitution's salience and noting who, when, and for what purposes made it go global. Current analyses of globalisation are incomplete or incorrect because they all consistently and wholly overlook the Constitution's catalyzing role or simplify the purposes served by economic globalization in ways that diminish the Constitution's importance. Accordingly, an international constitutional law or constitutional political economy lens is indispensable to exploring Globalisation no matter what our perspective is, mainstream or Third World. This chapter sets out the mission for the book: to provide the politico-economic globalisation discourse with its missing parental foundation from a Third World Approaches to International Constitutional Law (TWAIL-CL) perspective. Toward this end, this chapter establishes the Constitution's salience and outlines its centrality to liberalism, neoliberalism, militarism, and colonialism, post-1989 UN Peacebuilding, the post-World War II's human rights regime and achieving the World Bank's policies (e.g., privatisation). This discussion sets the stage for exploring comprehensively how Globalisation has shaped the Security Council's functions and international law concepts of peace, justice, and human rights. In this way, this book simultaneously lays the foundation for Global Studies, a field that emerged from economic globalisation, starting from this chapter"--
Keywords: Economics; Development